Autophagy involvement in oncogenesis. Issue 11 (1st October 2020) - Torii, Satoru; Honda, Shinya; Murohashi, Michiko; Yamaguchi, Hirofumi; Shimizu, Shigeomi
Abstract: Various clinical and experimental findings have revealed the causal relationship between autophagy failure and oncogenesis, and several mechanisms have been suggested to explain this relationship. We recently proposed two additional mechanisms: centrosome number dysregulation and the failure of autophagic cell death. Here, we detail the mechanical relationship between autophagy failure and oncogenesis. Abstract : Various clinical and experimental findings have revealed the causal relationship between autophagy failure and oncogenesis. Here, we detail their mechanical relationship.